Do RadioAstron detections correlate with flaring states? An initial study of seven southern AGN. Issue 2 (15th January 2020) - Edwards, P.G.; Stevens, J.; Phillips, C.; Reynolds, C.; Kovalev, Y.Y.; Voitsik, P.; Sokolovsky, K.; McCallum, J.; Quick, J.; Ojha, R.
Abstract: We examine the state of seven southern radio sources at the time of their RadioAstron AGN Survey observations. Both ATCA flux density monitoring data and Fermi light-curves are considered in determining the relative activity of the source. A simple hypothesis, that sufficiently compact source structure exists for detections on RadioAstron baselines when the source is in a flaring state, is qualitatively tested. We find four instances of RadioAstron detections during flaring radio states and four instances of RadioAstron non-detections during fading or quiescent radio states, in support of the hypothesis. However, we also find three instances of RadioAstron detections during quiescent or fading radio states, and two non-detections during a flaring state, indicating that the situation is (not unexpectedly) more complex. Radio and gamma-ray monitoring such as that described here, together with the full RadioAstron AGN Survey results, will allow a more thorough investigation of the dependencies of detections on baselines of >10 Earth diameters.